GOTONG ROYONG AS POLITICAL PRAXIS: COLLECTIVE RESPONSIBILITY AND DEMOCRATIC ACTION - Adian, Donny Gahral (UI Scholars Hub, 2026)
This research explores gotong royong, an indigenous Indonesian concept of mutual cooperation, as an alternative political culture in the face of liberal individualism and capitalist competition. Drawing from the philosophical legacy of Soekarno, Indonesia’s founding president, the research situates gotong royong not merely as a traditional value, but as a dynamic political principle grounded in tolerance, solidarity, and social justice. Soekarno’s vision of democracy transcends procedural liberalism by emphasizing equal capabilities, not just equal opportunities, thereby addressing the structural and cultural barriers that hinder political participation for marginalized citizens. Through a comparative lens, the article juxtaposes the atomizing effects of liberalism—where personal rights become barriers to collective action—with gotong royong as a praxis of ethical responsibility and collective agency. It integrates Hannah Arendt’s distinction between labor, work, and action to highlight how gotong royong embodies a form of praxis that reveals the plurality and interdependence of human existence within public life. In this view, politics is not a battlefield of interests but a space for enacting shared values and sustaining communal well-being. The research also grounds its arguments in practical examples, notably the tanggung renteng cooperative model, a community-based economic system rooted in shared decision-making, risk-bearing, and responsibility. This system reflects the ethical dimensions of gotong royong, where mutual trust and empathy guide economic relations and prevent default through collective discipline. The model illustrates how economic participation can be democratized through cultural mechanisms rather than imposed market logic. Ultimately, the research contends that gotong royong is not a nostalgic relic but a forward-looking political imagination that revitalizes public life. It offers a philosophical and practical response to the erosion of social capital and the commodification of political space. As a living principle embedded in Indonesia’s constitutional ideals, gotong royong affirms that genuine political emancipation must be rooted in human solidarity and shared responsibility. The revitalization of this principle is essential for cultivating rational, empathetic, and initiative-taking citizens who act not out of self-interest, but for the collective good.